2001
DOI: 10.1152/ajpcell.2001.280.5.c1224
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ downregulates expression of Na+/H+ exchangers NHE2 and NHE3 in rat intestine and human Caco-2/bbe cells

Abstract: Diarrhea associated with inflammatory bowel diseases has traditionally been attributed to stimulated secretion. The purpose of this study was to determine whether chronic stimulation of intestinal mucosa by interferon-gamma (IFN-gamma) affects expression and function of the apical membrane Na(+)/H(+) exchangers NHE2 and NHE3 in rat intestine and Caco-2/bbe (C2) cells. Confluent C2 cells expressing NHE2 and NHE3 were treated with IFN-gamma for 2, 24, and 48 h. Adult rats were injected with IFN-gamma intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 29 publications
0
101
0
Order By: Relevance
“…Previous studies have shown that NHE3 can be downregulated by chronic IFN-g treatment (25). However, the lack of an effect of IFN-g alone on either water absorption or barrier function suggests that it does not play a role in the acute T cell-dependent diarrhea modeled here.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have shown that NHE3 can be downregulated by chronic IFN-g treatment (25). However, the lack of an effect of IFN-g alone on either water absorption or barrier function suggests that it does not play a role in the acute T cell-dependent diarrhea modeled here.…”
Section: Discussionmentioning
confidence: 61%
“…Interferon-γ and TNF-α decrease NHE3 activity causing diarrhea [51,145,2]. Consistent with a role in inflammatory bowel disease, NHE3 expression and/or activity is decreased in mouse models and human disease [159,187] .…”
Section: Slc9a3 -Nhe3mentioning
confidence: 68%
“…Once again proinflammatory cytokines are partially to blame. IFN-␥ and TNF-␣ (but not IL-1␤) decrease NHE3 activity and mRNA expression (7,112,125). This reduction may result from cAMP-dependent PKAmediated phosphorylation of Sp1 and Sp3 (transcription factors), which decreases their affinity for the gene promoter region (7).…”
Section: Nhe3 Is Impaired In Ibdmentioning
confidence: 99%